Spatial Perception and Navigation in the Absence of Vision - Daniel-Robert Chebat; Maurice Ptito (Sensors)
In congenital blindness (CB), tactile and auditory information can be reinterpreted by the brain to compensate for visual information through brain plasticity mechanisms triggered by training [...]